2022
DOI: 10.3390/plants11040500
|View full text |Cite
|
Sign up to set email alerts
|

The First Genetic Linkage Map of Winged Bean [Psophocarpus tetragonolobus (L.) DC.] and QTL Mapping for Flower-, Pod-, and Seed-Related Traits

Abstract: Winged bean [Psophocarpus tetragonolobus (L.) DC.] (2n = 2× = 18) is a tropical legume crop with multipurpose usages. Recently, the winged bean has regained attention from scientists as a food protein source. Currently, there is no breeding program for winged bean cultivars. All winged bean cultivars are landraces or selections from landraces. Molecular markers and genetic linkage maps are pre-requisites for molecular plant breeding. The aim of this study was to develop a high-density linkage map and identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Major QTL for pod length (qPoL3) and seed breadth (qSB4), length (qSL7.2) and thickness (qST9) mapped; previously reported QTL for pod length (qPoL8) and 100-seed weight (qSW8) and for seeds pod -1 (qSN9.2) confirmed Garcia-Oliveira et al, 2020 One major and six minor QTL associated with pod length Kongjaimun et al (2012b) Winged bean 31 QTL linked with pod length, pod colour, pod anthocyanin content, and flower and seed colour; the major QTL for pod colour, anthocyanin content, and calyx colour, and for seed colour and flower wing colour located at the same position Chankaew et al (2022) Frontiers in Genetics frontiersin.org important method for the breeding of crops to improve their productivity and resilience under stresses caused by climate change (Gramazio et al, 2021). It involves the integration of genetic materials from one species to another, often from a wild relative to a domesticated crop (Quezada-Martinez et al, 2021).…”
Section: African Yard Long Beanmentioning
confidence: 75%
See 2 more Smart Citations
“…Major QTL for pod length (qPoL3) and seed breadth (qSB4), length (qSL7.2) and thickness (qST9) mapped; previously reported QTL for pod length (qPoL8) and 100-seed weight (qSW8) and for seeds pod -1 (qSN9.2) confirmed Garcia-Oliveira et al, 2020 One major and six minor QTL associated with pod length Kongjaimun et al (2012b) Winged bean 31 QTL linked with pod length, pod colour, pod anthocyanin content, and flower and seed colour; the major QTL for pod colour, anthocyanin content, and calyx colour, and for seed colour and flower wing colour located at the same position Chankaew et al (2022) Frontiers in Genetics frontiersin.org important method for the breeding of crops to improve their productivity and resilience under stresses caused by climate change (Gramazio et al, 2021). It involves the integration of genetic materials from one species to another, often from a wild relative to a domesticated crop (Quezada-Martinez et al, 2021).…”
Section: African Yard Long Beanmentioning
confidence: 75%
“…the loss of shattering in domesticated rice (Konishi et al, 2006;Li et al, 2006), hard kernel coat in maize (Wang et al, 2005), and fruit size in tomato (Frary et al, 2000). High density linkage maps are available for several minor legumes, including adzuki bean (Han et al, 2005), Bambara groundnut (Gao et al, 2023), grass pea (Hao et al, 2022), lima bean (Garcia et al, 2021), and winged bean (Chankaew et al, 2022).…”
Section: Genetic Markers and Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, accession MYO-01 has quite small pods (a mature pod length of around 11 cm, half that of accessions CHIMBU and MYAN-05), but studies elsewhere have shown that high vegetable pod yields are correlated with pod length and weight more so than with pod number (Kesavan and Erskine 1980, in Papua New Guinea;Yulianah et al 2020, in Indonesia). Similar germplasm evaluations in various locations have shown considerable diversity in pod characteristics, including pod length, width and weight, and pod color, shape, and texture (Khan 1982;Kuswanto et al 2016;Kant and Nandan 2018;Sarode Hemal and Dodake 2019;Adegboyega et al 2019Adegboyega et al , 2021Laosatit et al 2021;Chankaew et al 2022) that could provide nutritional diversity and novelty in competitive commercial vegetable markets.…”
Section: Discussionmentioning
confidence: 99%
“…The WB has green pod productivity of up to 10 t/ha and tuber productivity of up to 11 t/ha [5]. The WB tuber (WBT) has 20% CP, 3.0% crude fiber (CF), 0.6% fat, and a high starch level of 25-30% (energy = 3.82 Mcal/kg) [6,7], which should make it a suitable alternative for animal feed [3].…”
Section: Introductionmentioning
confidence: 99%